Effect of SiCN passivation on electromigration reliability of nanotwinned Cu redistribution lines - Yu-Wen Hung; Mai-Phuong La; Yi-Quan Lin; K.N. Tu; Chih Chen (Journal of Materials Research and Technology)
Nanotwinned Cu (NT-Cu), with numerous advantages, is highly suitable for implementation in Cu redistribution lines (RDLs). However, oxidation is a significant reliability concern as it accelerates resistance increase and shortens the electromigration (EM) lifetime of fine-pitch NT-Cu lines. In this study, bare NT-Cu RDLs exhibited a rapid oxide layer growth, which caused a sharp rise in resistance. To prolong the EM lifespan of NT-Cu RDLs and reduce the thermal budget, plasma-enhanced chemical vapor deposition (PECVD) SiCN was applied to passivate NT-Cu surfaces at a low operating temperature of 150 °C. The SiCN layer effectively inhibited oxidation during EM tests at 200 °C by 1.0 × 106 A/cm2, resulting in a significant enhancement in the longest EM failure time and mean time to failure (MTTF or T50). The longest EM failure time and T50 of SiCN-covered NT-Cu lines achieved 4433 h and 1930 h, respectively. Compared to other passivation options, such as TiO2, polyimide (PI), and graphene, the SiCN layer demonstrated the highest effectiveness in extending the EM lifetime of NT-Cu lines. This study presents a viable passivation approach for NT-Cu applications and highlights the SiCN coating layer as a superior choice for enhancing the EM reliability of NT-Cu RDLs.